Pharmageddon by David Healy - Bauer, Henry (Journal of Scientific Exploration, 2015)
This book is a fully documented exposé of the considerable damage being done to health by modern “scientific” drug-based medical practice. The author is a psychiatrist whose earlier books include Mania: A Short History of Bipolar Disorder, Shock Therapy: The History of Electroconvulsive Treatment in Mental Illness, The Creation of Psychopharmacology: The Discovery and Development of Antipsychotic Medication, and The Antidepressant Era: The First Complete Account of the Phenomenon of Antidepressants. These described how psychiatry had gone badly wrong by fixating on drugs and misinterpreting what they do, and how the pharmaceutical industry (Big Pharma) fought against acknowledging the harm done by these drugs, notably increased rates of suicide and significant decreases in expected lifespan. In this new book, Healy extends the critique to drug-based medicine across the board.